2010
DOI: 10.1097/smj.0b013e3181e6dabf
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Immunity: Relationship of Lymphocyte Count and Apnea Hypopnea Index

Abstract: We found OSA-induced sleep interruption not associated with lymphocyte, neutrophil, or peripheral blood cell count alterations. This information is useful for researchers evaluating the influence of sleep disruption on immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…In accordance to our results, Freire et al found no association of AHI with total lymphocyte, neutrophil, or peripheral blood cell count alterations [9]. Recently, many investigators raised the notion of a Th17/Treg balance and reported an imbalance in patients with various autoimmune and inflammatory diseases [1417].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance to our results, Freire et al found no association of AHI with total lymphocyte, neutrophil, or peripheral blood cell count alterations [9]. Recently, many investigators raised the notion of a Th17/Treg balance and reported an imbalance in patients with various autoimmune and inflammatory diseases [1417].…”
Section: Discussionsupporting
confidence: 91%
“…OSAS is involving various immune cells, particularly T lymphocytes [9, 10]. Activation of T lymphocytes is among the crucial steps leading to the release of inflammatory mediators and adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This point can be viewed as a limitation of our study. Otherwise, some researchers suggested that obesity, rather than 'hypoxia/reoxygenation' phenomenon, may be the main origin of inflammation in OSA [3,4,[18][19][20][21][22]. Additionally, there are contradictory opinions regarding this phenomenon [13,14].…”
Section: Discussionmentioning
confidence: 96%
“…While the sudden opening of the upper airway, inspiratory air pressure causes tissue damage and local inflammation due to mechanical trauma, episodic hypoxemia, and reoxygenation induces the tonic elevation of sympathetic nervous system, oxidative stress, hypercoagulable, endothelial dysfunction, and systemic inflammation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, intermittent and chronic hypoxia has been associated with glucose intolerance and insulin resistance [41, 42], and the adverse effects of hypoxia on glucose metabolism appear to be mediated via the sympathetic nervous system [39, 43]. In addition, to effects on physiological processes, the sleep disruption associated with SDB has effects that are often very debilitating, including daytime sleepiness [44], cognitive impairment [45, 46], depression [47], relationship difficulties [48] and dementia [46] to appetite changes/obesity [49] and reduced immunity [50]. …”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%